Do preliterate children spontaneously employ spatial coding for serial order in working memory? - Dijck, Jean‐Philippe; Abrahamse, Elger; Fias, Wim (Annals of the New York Academy of Sciences, 2020)
The ability to memorize arbitrary sequences contributes to cognitive faculties like language and mathematics. Research suggests that in literate adults, serial order in verbal working memory (WM) is grounded in spatial attention and is mentally organized according to our reading habits, that is, from left‐to‐right in Western cultures. Currently, it is unknown whether spatialization is a consequence of literacy, or whether the ability already exists early in life but is shaped by literacy in “calibrating” the initial individual differences in the orientation of spatial coding. Here, we investigated the spatial coding of serial order in WM in 5‐year‐old children who did not yet enter formal literacy education. At the group level, no systematic spatial coding was observed. To investigate whether this absence was due to subjects with reliable but opposing effects, we determined the prevalence of spatial coding at the individual level. This analysis revealed that 36% of the children systematically associated serial order to space, with approximately half of them coding from left‐to‐right and the rest from right‐to‐left. These results indicate that a subgroup of preliterate children associate serial order with space and suggest that reading and writing experience calibrates the orientation of spatial coding with reading habits. Here, we investigated the spatial coding of serial order in working memory in 5‐year‐old children who did not yet enter formal literacy education. The results indicate that a subgroup of preliterate children associate serial order with space and suggest that reading and writing experience calibrates the orientation of spatial coding with our reading habits.